Beyond age stereotypes: Unveiling the investment intentions of young individuals during the COVID-19 pandemic - Puspawati, Dewita; Abas, Novel Idris; Permatasari, Widowati Dian (International Journal of Management and Sustainability, 2024)
This study examines personality traits, financial literacy, and risk tolerance for investment intentions. In addition, this study also examines the role of risk tolerance as a mediator in the influence of personality traits on investment intentions. A quantitative research method is used to measure personality traits, financial literacy, risk tolerance, and investment intention. A survey was conducted among young individuals in Indonesia. Respondents came from various regions in Indonesia, especially those from Java, Indonesia. The number of samples was 405 questionnaires. The results show that several personality traits, such as extraversion, neuroticism, and openness, affect investment intentions. However, the results show conscientiousness and agreeableness do not affect investment intentions. Researchers have found that extraversion and conscientiousness do not affect risk tolerance, but neuroticism, openness, and agreeableness do. Financial literacy and risk tolerance are also proven to affect investment intentions. When the mediation effect was tested, it was found that neuroticism, openness, and agreeableness affect investment intentions. On the other hand, risk tolerance does not act as a mediator variable between extraversion and investment intention. The practical implication of the study lies in assisting stock exchanges in developing countries to craft effective strategies for attracting Generation Z and Alpha investors, particularly during periods of economic volatility.